2020
DOI: 10.1016/j.celrep.2019.12.075
|View full text |Cite
|
Sign up to set email alerts
|

Periostin Promotes Colorectal Tumorigenesis through Integrin-FAK-Src Pathway-Mediated YAP/TAZ Activation

Abstract: Highlights d Periostin deficiency inhibits colorectal tumor formation in mice d Periostin is mainly secreted by fibroblasts to promote tumor cell proliferation d Periostin promotes YAP/TAZ nuclear localization and IL-6 expression in tumor cells d IL-6 promotes fibroblast activation and periostin expression during tumorigenesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(119 citation statements)
references
References 47 publications
(60 reference statements)
4
99
0
Order By: Relevance
“…A previous study described that a mutant cell line lacking YAP showed decreased Thbs1 levels along with down-regulation of YAP target genes and FA molecules, indicating that Thbs1 may act as a feedforward driver for YAP signaling (41). Interestingly, the proteolytic remodeling of laminin-1 has been shown to modulate awakening of dormant cancer cells through integrin/FAK/ERK/MLCK (myosin lightchain kinase)/YAP signaling (42), and fibroblast-derived periostin (encoded by Postn) has been shown to mediate colorectal tumorigenesis through integrin/FAK/Src/YAP signaling (43), further supporting the idea that an ECM can regulate YAP signaling in various biological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study described that a mutant cell line lacking YAP showed decreased Thbs1 levels along with down-regulation of YAP target genes and FA molecules, indicating that Thbs1 may act as a feedforward driver for YAP signaling (41). Interestingly, the proteolytic remodeling of laminin-1 has been shown to modulate awakening of dormant cancer cells through integrin/FAK/ERK/MLCK (myosin lightchain kinase)/YAP signaling (42), and fibroblast-derived periostin (encoded by Postn) has been shown to mediate colorectal tumorigenesis through integrin/FAK/Src/YAP signaling (43), further supporting the idea that an ECM can regulate YAP signaling in various biological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, high expression of POSTN, also overrepresented in PUC-GBC2, might explain the higher migratory ability of these cells. POSTN encodes for periostin, a multifunctional ECM protein that contributes to the remodeling of the tumor microenvironment during tumor progression [36]. In CCA and hepatoblastoma, overexpressed periostin was found to induce cell migration and epithelial-to-mesenchymal transition (EMT) features [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, TGFbeta-activated CAFs may secrete POSTN in order to increase proliferation, motility, and invasive properties in head and neck cancer (HNC) cells (Qin et al, 2016). Similarly, CAF-secreted POSTN may also promote tumor progression in CRC through YAP/TAZ activation in cancer cells (Ma et al, 2020). Of note, Deng and colleagues showed that the YAP-activated Wnt/βcatenin pathway promotes colon tumorigenesis (Deng et al, 2018).…”
Section: Metastatic Cancer Cells Spreadingmentioning
confidence: 99%